2020
DOI: 10.1016/j.chaos.2020.110120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of deep learning approaches to predict COVID-19 infection

Abstract: Highlights To provide a prediction study for COVID-19 disease with deep learning application models with laboratory findings rather than X-ray or CT images. To ensure the prediction model for this novel pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
238
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(269 citation statements)
references
References 41 publications
1
238
0
5
Order By: Relevance
“…Normally, in the artificial intelligence studies with relatively small datasets, cross-validation method is mostly preferred. But especially in medical clinical application, this cross-validation approach gives fewer clear results [29] . In this study, to have a clearer result, the tests were realized using train–test split approach and cross-validation approach was not preferred.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, in the artificial intelligence studies with relatively small datasets, cross-validation method is mostly preferred. But especially in medical clinical application, this cross-validation approach gives fewer clear results [29] . In this study, to have a clearer result, the tests were realized using train–test split approach and cross-validation approach was not preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Alakus and Turkoglu used a laboratory data set that contains 600 samples to compare deep learning approaches for prediction of COVID-19. The experimental results were obtained as 92.30% accuracy, 93% F1-score, 92.35% precision, 93.68% recall and 90% AUC [29] .…”
Section: Literature Reviewmentioning
confidence: 99%
“… Zeroual et al, 2020 , Tomar and Gupta, 2020 , Czarnowski et al, 2008 , El Zowalaty and Järhult, 2020 , Shahid et al, 2020 , Hewamalage et al, 2021 , Jiménez et al, 2020 , Kaushik et al, 2020 , BhedadJamshidi et al, 2020 , Ribeiro et al, 2020 , Naudé, 2020 , Arora et al, 2020 , Ribeiro et al, 2020 , Ogundokun et al, 2020 , Alzahrani et al, 2020 , Shastri et al, 2020 , Alakus and Turkoglu, 2020 , Papastefanopoulos et al, 2020 , Chimmula and Zhang, 2020 , Wang et al, 2020 , Wang et al, 2020 , DataGov , Car et al, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Other example of the research that use DNN in predicting the trend of the pandemic can be found in [424] , [425] , [426] , [427] , [428] , [429] .…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%